Perspectives of development of the system of quality assurance of employees vocation training results in Ukraine - Дрозач, М. І.; Стульпінас, Н. К. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2018)
The article deals with the problems of ensuring the quality of the results of vocational training in production and ways to improve the level of professional training of workers, in particular, through the use of modular training technology. Based on the results of the survey of employers, proposals are presented for the improvement of certain regulatory and legal documents.